Religious concepts in the works of Shakarim (Eurasian Journal of Philology Science and Education, 2019)
The article defines the meaning of religious concepts and names in the works of Shakarim Kudaiberdiev and their significant meaning. The article defines the features and features of the phonetic, morphological features along with Islamic concepts in the works. This also explains the creative contribution ofShakarim Kudaiberdiev to the formation and formation of the Kazakh literary language at the beginningof the 20th century in the written tradition. The article describes the terminological nature of religiousconcepts in the works of Sh. Kudaiberdiev and is relatively revealed on the basis of common religiousnames and religious names, rarely found in literary language. As you know, the whole set of words in acommon language is a language dictionary. That is, social and popular religious concepts can be dividedinto active and passive words, depending on the frequency of use of words in a dictionary. Active wordsare not only understood by people who speak a certain language, but also clearly defined in their speech,whereas passive words are clear, but not used in a language.